2021
DOI: 10.1200/jco.2021.39.3_suppl.171
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of early-onset gastric and esophagus cancers has changed over time with disproportionate impact on Black and Hispanic patients.

Abstract: 171 Background: The increased incidence of gastro-esophageal junction adenocarcinoma has been well-described, but how the proportion of early versus older onset cancer has changed over time remains incompletely understood. This study characterized the socioeconomic and pathologic characteristics of early-onset gastro-esophageal malignancies. Methods: All patients with gastric cancer (GC) and esophageal cancer (EC) from 2004-2015 in the National Cancer Database were included and categorized by age under or ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A trend toward higher MSI-High status in average-onset was demonstrated. Another study addressed socioeconomic and pathologic characteristics of EOEGC in the NCD and revealed that EOEGC (defined < 60 y) tend to be African-American or Hispanic and to have an advanced disease at presentation [61]. An optimistic note with regard to early-onset pancreatic cancer (EOPC) derives from a study which appraised clinical characteristics of EOPC (<60 y) retrieved from the NCD and compared to average-onset.…”
Section: Highlights In Adolescent and Young Adults Eortc Adolescent And Young Adults Task Force: Irit Ben-aharonmentioning
confidence: 99%
“…A trend toward higher MSI-High status in average-onset was demonstrated. Another study addressed socioeconomic and pathologic characteristics of EOEGC in the NCD and revealed that EOEGC (defined < 60 y) tend to be African-American or Hispanic and to have an advanced disease at presentation [61]. An optimistic note with regard to early-onset pancreatic cancer (EOPC) derives from a study which appraised clinical characteristics of EOPC (<60 y) retrieved from the NCD and compared to average-onset.…”
Section: Highlights In Adolescent and Young Adults Eortc Adolescent And Young Adults Task Force: Irit Ben-aharonmentioning
confidence: 99%